Marketing Strategy of Teaching Hospital: Challenges For Teaching Hospitals in Indonesia - Ardiansyah Ardiansyah; Amal Chalik Sjaaf (Syntax Corporation, 2023)
The increasing demands of the community for quality and affordable health services make hospitals have to always try to survive amid increasing competition. This article is a systematic review where data is taken from online databases such as ProQuest, Wiley Online, JStore, ScienceDirect, Embase, Scopus, and local journals (Garuda Portal, Jurnal Promkes) using the keywords